WILD NATIVE PLANTS IN URBAN ECOSYSTEMS AROUND JAKARTA: A CHECKLIST OF THE WOODY SPECIES OF UNIVERSITAS INDONESIA - Wendy Achmmad Mustaqim; Nisyawati (Jurnal Pro-Life, 2020)
A study has been conducted on the diversity of woody plants which are wild and native in Universitas Indonesia,an urban ecosystem in the area of Jakarta Capital Region. This work is part of the flora inventory in UniversitasIndonesia. A number of 118 species (34 families) were recorded, with three largest families are Fabaceae (14species), Moraceae (12 species) and Phyllanthaceae (10 species). Among those numbers, 26 species are climbers,which is considerably remarkable for urban ecosystem. Twenty four were considered as lowland species. Fivewere exclusively distributed in Western Java. Twenty six species have been included in Flora van Batavia whichshowed that Universitas Indonesia will be an important component for the conservation of plants diversity inJakarta and surroundings. An estimation on abundance also given for all species recorded, which resulting thatabout 41.52% species were locally rare. Discussion in future conservation in local scales also briefly discussed.Two species, namely Helicteres viscida and Phoebe declinata, are proposed for main conservation priorities ofwild and native woody plants species in Universitas Indonesia. Keywords: checklist, Jakarta, native species, urban biodiversity, woody plants